Hepatoid carcinoma of the ovary: A case report and review of the literature - Laura K. Randolph; Maeve K. Hopkins; Michael P. Hopkins; Daniel A. Wasdahl (Elsevier, 2015)
Primary hepatoid carcinoma of the ovary (HCO) is a rare aggressive tumor that typically presents at an advanced stage in postmenopausal women with unilateral or bilateral ovarian masses and elevated AFP and CA125. We report a case of HCO in a 73 year-old woman who presented with abdominal distention, weight loss, and a large lower abdominal mass. Postoperative serum AFP was markedly elevated and trended down with initiation of chemotherapy. Review of the literature revealed thirty-two reported cases with no consensus on histogenesis or consistent immunohistochemical profile other than positive AFP staining in all but one case. Although the optimal treatment has not yet been determined, tumor debulking surgery followed by a platinum and taxane based chemotherapy regimen has shown promise. Both serum AFP and CA125 appear to have prognostic value and can be used to follow response to treatment and screen for recurrence.